2012
DOI: 10.1097/igc.0b013e31823fd413
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Chemotherapy for Stage I Clear Cell Carcinoma of the Ovary

Abstract: The current study was performed only in fully staged patients, suggesting that postoperative adjuvant chemotherapy is not necessary for stage IA CCC patients. For patients with stage IC CCC patients, adjuvant chemotherapy suppressed recurrence, but the effectiveness was insufficient in our limited study. Further studies are required to clarify this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 16 publications
(6 reference statements)
2
27
0
Order By: Relevance
“…However, early stage CCC confined within the ovary has excellent prognosis, 95% survival for surgical stage IA disease [12]. A retrospective study with 73 patients with CCC by Takada et al showed that postoperative adjuvant chemotherapy might not be necessary for stage IA CCC patients [21]. However, current evidence is not strong enough to change the treatment guidelines, which recommend that all patients with CCC, including stage IA or IB disease, receive postoperative adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 98%
“…However, early stage CCC confined within the ovary has excellent prognosis, 95% survival for surgical stage IA disease [12]. A retrospective study with 73 patients with CCC by Takada et al showed that postoperative adjuvant chemotherapy might not be necessary for stage IA CCC patients [21]. However, current evidence is not strong enough to change the treatment guidelines, which recommend that all patients with CCC, including stage IA or IB disease, receive postoperative adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 98%
“…It is important to note, however, that because of the small numbers, these data can be incorporated into a risks-and-benefits discussion but do not replace standard staging guidelines. Takada et al 13 published survival and recurrence data on 73 patients with stage I OCCC who were comprehensively staged during a 9-year study period. On multivariate analysis, positive washings and/or ovarian surface involvement were independently related to both overall survival and progression-free survival regardless of adjuvant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Mizuno et al 16 reported that the 5-year RFS rates in CCC patients who received comprehensive surgical staging and were treated with/ without adjuvant chemotherapy were 93.8% (n = 16) and 100% (n = 25) for stage IA, and 86.6% (n = 75) and 94.1% (n = 18) for stage IC1, respectively, and concluded the routine adjuvant chemotherapy after comprehensive surgical staging may be unnecessary for patients with at least stage IA. Takada et al 23 reported outcome of stage I CCC patients who received comprehensive surgical staging consisting of 4 with stage IA and 11 with stage IC1 who received adjuvant chemotherapy and 16 with stage IA and 16 with stage IC1 who received no additional therapy. It was reported that no recurrence was observed in stage IA patients and that the 5-year RFS and OS rates in stage IC1 patients were 87.5% and 100% in the adjuvant chemotherapy group and 74.0% and 76.4% in the observation group, respectively, and suggested that postoperative adjuvant chemotherapy is not necessary for stage IA CCC patients but that adjuvant chemotherapy suppressed recurrence for stage IC CCC.…”
Section: Discussionmentioning
confidence: 99%